2008
DOI: 10.1007/s10342-008-0238-2
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and pathogenicity of fungi in necrotic and non-symptomatic shoots of declining common ash (Fraxinus excelsior) in Sweden

Abstract: Currently, massive dieback of Fraxinus excelsior is observed in countries of eastern, northern and central Europe, and the reasons for it are unclear. The aims of the present work were (a) to study fungal communities in declining F. excelsior crowns; (b) to clarify role of fungi in the decline. Shoots from symptomatic crowns were collected in four localities in central Sweden, and distributed into the following categories: (a) visually healthy; (b) initial necroses; (c) advanced necroses; (c) dead tops. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
143
1
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(158 citation statements)
references
References 21 publications
(29 reference statements)
9
143
1
5
Order By: Relevance
“…Similar results were reported from Sweden (Bakys et al 2009a, b). Most species that occurred commonly in this study have been found on stems and twigs of F. excelsior in various habitats (Butin and Kowalski 1986;Griffith and Boddy 1988, 1991Lygis et al 2005;Bakys et al 2009a;Chen 2012;Davydenko et al 2013).…”
Section: Fungal Diversitymentioning
confidence: 99%
See 3 more Smart Citations
“…Similar results were reported from Sweden (Bakys et al 2009a, b). Most species that occurred commonly in this study have been found on stems and twigs of F. excelsior in various habitats (Butin and Kowalski 1986;Griffith and Boddy 1988, 1991Lygis et al 2005;Bakys et al 2009a;Chen 2012;Davydenko et al 2013).…”
Section: Fungal Diversitymentioning
confidence: 99%
“…A similarly high diversity of fungi on ash with dieback has been recorded by others. In Sweden, Bakys et al (2009a) identified 56 fungal taxa on shoots of 20-to 30-year-old F. excelsior trees with various dieback symptoms, and in New Zealand, Chen (2012) identified 90 fungal taxa in bark and wood or buds of symptomless twigs of 60-to 70-year-old F. excelsior. In contrast, the base of dead twigs was colonized by only 22 species in healthy, naturally pruned F. excelsior trees (Butin and Kowalski 1986).…”
Section: Fungal Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…European ash (Fraxinus excelsior L.) is threatened by ash dieback, a disease caused by the fungus Hymenoscyphus fraxineus (BARAL et al, 2014), occurring first in Poland and meanwhile in most parts of Europe (PUKACKI and PRZYBYL, 2005;BAKYS et al, 2009a;WOOD-WARD and BOA, 2012;VASAITIS et al, 2013). The origin of the fungus was unknown until recently when it was proved to originate from East Asia, where it is a saprophytic fungus and plays a similar ecological role on F. manshurica as H. albidus on F. excelsior (VASAITIS et al, 2013;ZHAO et al, 2012).…”
Section: Genetic Analysis Of European Common Ash (Fraxinus Excelsior mentioning
confidence: 99%